Some physiological and Bichemical responses to cadmium in salicylic acid applied cucumber (Cucumis sativus L.) seedlings - Çanakci, Songül; Karabo?a, Zeynep (My University, 2013)
In this study, the probability of salicylic acid (SA), serving as a mediator for protecting plants against cadmium (Cd) toxicity, was investigated. In cucumber seedlings exposed to increasing Cd concentrations (0, 25, 50 and 100 ?M), the seedling and leaf elongation growth reduced, whereas the fresh and dry weight accumulation decreased. Furthermore, the levels of some important parameters regarding oxidative stress in the leaves of the seedlings, namely lipid peroxidation (MDA) increased, while reduced glutathione (GSH), fatty acid methyl esters (FAME) and the photosynthetic pigment content decreased. In the leaves of seedlings, which were pre-applied with salicylic acid (0.75 mM), alleviated the negative effects of Cd on MDA and GSH. The SA pre-application caused different effects due to the Cd concentration on GSH and FAME. The beneficial effect of SA on the oxidative damages caused by Cd was mainly found rather significant for 25 and 50 ?M. Our data indicated that in reducing the negative results of oxidative stress caused by the toxicity of this heavy metal, SA may have beneficial effects.